2015
DOI: 10.2214/ajr.14.13098
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time MRI-Guided Focused Ultrasound for Focal Therapy of Locally Confined Low-Risk Prostate Cancer: Feasibility and Preliminary Outcomes

Abstract: MRI-guided focused ultrasound is a feasible method of noninvasively ablating low-risk prostate cancers with low morbidity. Further investigation and follow-up are warranted in a larger patient series with appropriate statistical analysis of oncologic and functional outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…Magnetic Resonance Imaging (MRI)-guided Focused Ultrasound (MRgFUS) is a non-invasive, non-ionizing ablation modality, which is used to treat various tumors [35], neuropathic pain [6] and painful bone metastasis [7]. Additionally, multiple research studies have focused on the ability of FUS to disrupt nerve conduction and cause necrosis of nerves [8, 9], including MRgFUS renal sympathetic denervation [10], abltation of sciatic [11, 12] and intercostal [13] nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI)-guided Focused Ultrasound (MRgFUS) is a non-invasive, non-ionizing ablation modality, which is used to treat various tumors [35], neuropathic pain [6] and painful bone metastasis [7]. Additionally, multiple research studies have focused on the ability of FUS to disrupt nerve conduction and cause necrosis of nerves [8, 9], including MRgFUS renal sympathetic denervation [10], abltation of sciatic [11, 12] and intercostal [13] nerves.…”
Section: Introductionmentioning
confidence: 99%
“…mpMRI performed better than PSA measurements in the detection of residual tumor after therapy. Similar data for real-time MRI-guided focused ultrasound has been reported demonstrating the feasibility and low morbidity of this technique in focal therapy of localized low-risk prostrate cancer [84]. Le Nobin and colleagues found that a 9 mm treatment margin around the MRI visible lesion is needed to consistently ensure treatment of entire histological tumor volume during focal therapy [85].…”
Section: Imaging In Focal Therapymentioning
confidence: 64%
“…Magnetic resonance guidance has advantages over US, particularly superior depiction of anatomic detail . Magnetic resonance thermometry depicts the changes that occur within hydrogen atoms when they are subjected to heat. These changes can be recorded with phase shift imaging, chemical shift imaging, diffusion, spectroscopy, or even contrast agents added to the tissues …”
Section: Magnetic Resonance Versus Us Guidance For Hifumentioning
confidence: 99%